Modulation of mRNA expression and activities of xenobiotic metabolizing enzymes, CYP1A1, CYP1A2, CYP2E1, GPx and GSTP1 by the Salicornia freitagii extract in HT-29 human colon cancer cells - Altay, Ahmet; İrtem Kartal, Deniz and Sadi, Gökhan and Güray, Tülin and Yaprak, Ahmet Emre (Archives of Biological Sciences, 2017)
Phase I-II detoxification and antioxidant enzymes are responsible for the detoxification and elimination of activated carcinogens, acting as important biomarkers for chemoprevention. Among them, cytochrome P450s plays a prominent role in the metabolic activation of xenobiotics. The herb Salicornia freitagii (SF) (Amaranthaceae) is known for its anticancer, antioxidant, antidiabetic and antiinflammatory activities. In this study, we determined the bioactive phenolics in the SF methanol extract and investigated its antiproliferative potential in HT-29 human colon cancer cells. We also investigated the modulation of some phase I and II enzyme (CYP 1A1, 1A2, 2E1, GSTP1 and GPx) mRNA expression and enzymatic activities by the SF extract and its major bioactive phenolic compounds. LC/MS-MS analysis showed that the main phenolic compounds of the methanolic SF extract are vanillic acid (48 µg/100g) and p-coumaric acid (10.8 µg/100g). SF extract, vanillic acid and p-coumaric acid exhibited high antiproliferative activities in HT-29 cells, with IC50 values of 81.79µg/mL, 98.8 µM and 221.6 µM, respectively. The mRNA expression levels of CYP1A2 and CYP2E1 were decreased, while those of GSTP1 and GPx in HT-29 cells were increased after application of either the SF extract or vanillic acid. The SF extract by itself also increased the activities of GPx and GSTP1 enzymes 1.68- and 1.49-fold, respectively. Our data indicate that the SF extract and its major bioactive compound, vanillic acid, could exert a modulatory effect on the expression of enzymes that are involved in xenobiotic activation and detoxification pathways in the gastrointestinal tract. For this reason, SF can be considered as a natural source of chemopreventive agents. https://doi.org/10.2298/ABS160825118A Received: August 25, 2016; Revised: October 8, 2016; Accepted: October 13, 2016; Published online: November 3, 2016 How to cite: Altay A, İrtem Kartal D, Sadi G, Güray T, Yaprak AE. Modulation of mRNA expression and activities of xenobiotic metabolizing enzymes, CYP1A1, CYP1A2, CYP2E1, GPx and GSTP1 by the Salicornia freitagii extract in HT-29 human colon cancer cells. Arc Biol Sci. 2017;69(3):439-48.